Building an omnichannel in retailing / Muhammad Hanif Abdul Gafar and Nor Amira Mohd Ali - Abdul Gafar, Muhammad Hanif; Mohd Ali, Nor Amira (Universiti Teknologi MARA, Kedah, 2022)
The 21st century environment has widened an opportunity for any business, regardless of their industries. All traditional methods and concepts in business transactions have become more dynamic and flexible due to rapid growth and robust technologies. Presently, most consumers will spend their time online in activities, including shopping. According to Surin (2022), an average Malaysian spends nine hours and eighteen minutes daily browsing the internet, which equates to 141 days a year. Malaysians also spend three hours and one minute a day on social media equating to 46 days a year. Additionally, Malaysia ranked sixth among the world’s top 10 countries spending the most time on their screens (Surin, 2022). This phenomenon has not only happened in Malaysia but has affected businesses around the globe. Thus, global retailers have adapted and tuned their daily business transactions and activities into more digitalised platforms to reach the mass market easily.